Particulate Matter Adsorbants: Renewable Lanthanide Ionic Liquid/Polymer Composites for High‐Efficient Adsorption of Particulate Matter (Adv. Mater. Interfaces 1/2018). Issue 1 (10th January 2018) - Song, Kang‐Xiang; He, Ling; Zhang, Lei; Tao, Guo‐Hong
Abstract : Hybrid polymer materials based on lanthanide ionic liquids were prepared and applied as high‐efficiency and environmental friendly adsorbing materials for particulate matter (PM) adsorption by Guo‐Hong Tao and co‐workers in article number 1700448 . Ln‐10PVP materials can effectively absorb PM2.5 and PM10 in the air with >99% absorption efficiency. They can work at above 90% removal efficiency for 15 hours, and can be regenerated without obvious reduction on PM adsorption capacity.